تصميم وسائل وتكنولوجيا لتنمية مهارات القراءة في تعليم عن بعد للمرحلة الابتدائية - Uswatun Sovina; Khofifah Nadiatur rahma; Mulyadi Mulyadi (Qawa’id: Jurnal Bahasa dan Sastra Arab, 2026)
This study aims to examine the effect of integrating technological media and digital technologies into the development of reading skills among elementary school students. The study focuses on the use of digital books, multimedia, educational applications, flashcards, online learning platforms, and interactive educational games in distance learning environments. It addresses the persistent problem of students' limited reading proficiency, particularly in word recognition, reading fluency, and reading comprehension, despite the implementation of conventional instructional approaches. Therefore, the study highlights the need for innovative technology-based strategies that enhance reading instruction. This research employed a descriptive qualitative approach through the analysis of relevant literature and previous studies concerning the use of educational technology in Arabic language learning. The findings indicate that technological media significantly enhance students' motivation to learn, improve letter and word recognition, increase reading fluency, and strengthen reading comprehension by providing interactive learning environments, immediate feedback, and individualized learning opportunities. Furthermore, the effectiveness of distance learning is influenced by the availability of adequate technological infrastructure, teachers' competence in integrating digital tools, and parental support throughout the learning process. The study recommends expanding the integration of educational technology in Arabic language instruction and providing continuous professional development for teachers to design interactive reading activities appropriate to the developmental characteristics of elementary school learners, thereby improving learning outcomes and responding to the demands of the digital era.